2018
DOI: 10.1139/apnm-2018-0141
|View full text |Cite
|
Sign up to set email alerts
|

Are Canadian protein and physical activity guidelines optimal for sarcopenia prevention in older adults?

Abstract: Aging is characterized by physiological and morphological changes that affect body composition, strength, and function, ultimately leading to sarcopenia. This condition results in physical disability, falls, fractures, poor quality of life, and increased health care costs. Evidence suggests that increased consumption of dietary protein and physical activity levels, especially resistance exercise, can counteract the trajectory of sarcopenia. Canadian guidelines for protein intake and physical activity were last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 99 publications
(136 reference statements)
0
20
0
6
Order By: Relevance
“…Current recommendations for the treatment and prevention of sarcopenia include adequate protein intake and RE (Cruz-Jentoft et al, 2014; Deutz et al, 2014; Oliveira et al, 2018); however, encouraging older adults to change their dietary habits and engage in RE is challenging (Burton et al, 2017; Chao et al, 2000; Cohen-Mansfield et al, 2003; Crombie et al, 2004; Moran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations for the treatment and prevention of sarcopenia include adequate protein intake and RE (Cruz-Jentoft et al, 2014; Deutz et al, 2014; Oliveira et al, 2018); however, encouraging older adults to change their dietary habits and engage in RE is challenging (Burton et al, 2017; Chao et al, 2000; Cohen-Mansfield et al, 2003; Crombie et al, 2004; Moran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“… 10 While strength training is recommended in current PA guidelines, they focus primarily on general PA rather than targeted exercise. 11 It is therefore important to understand associations of general PA with sarcopenia and falls. The aim of this study was to determine associations of accelerometer-determined total duration and number of bouts of sedentary behavior, LPA, and MVPA with EWGSOP2-defined sarcopenia and its components, as well as their associations with incidence of falls over 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, almost half of the elderly Chinese population did not meet the individual protein intake requirement, which may result in serious adverse consequences for healthy aging. Furthermore, epidemiological studies have suggested that current dietary protein intake recommendations may be insufficient for maintaining muscle mass and strength for the elderly and for improving their health [20,21]. The requirement for a larger dose of protein to generate responses in elderly adults similar to those in younger adults provides the support for a beneficial effect of increased protein intake in older populations [22].…”
Section: Discussionmentioning
confidence: 99%